A Cross-Sectional Study of the Plantar Flexor Muscle and Tendon during Growth - Kubo, K.; Teshima, T.; Hirose, N.; Tsunoda, N. (International Journal of Sports Medicine, 2014)
The purpose of this study was to investigate growth changes in human plantar flexor muscle and tendons. In addition, we ascertained whether growth changes in muscle and tendon were more closely related to skeletal age than chronological age. 22 elementary school children (ESC), 19 junior high school students (JHS), and 23 young adults (ADT) men participated in this study. Maximal strain and hysteresis of tendon structures and cross-sectional area of Achilles tendon were measured using ultrasonography. In addition, skeletal age was assessed using Tanner-Whitehouse III method. Maximal strain of ESC was significantly greater than that of other groups, while no significant difference was observed between JHS and ADT. There was no difference in hysteresis among 3 groups. Relative cross-sectional area (to body mass2/3) of ADT was significantly smaller than that of other groups. For ESC and JHS, measured variables of muscle and tendon were significantly correlated to both chronological and skeletal ages. These results suggested that immature musculoskeletal system was protected by more extensible and larger tendon structures in ESC and only by larger tendon structures in JHS, respectively. Furthermore, there were no differences in correlation coefficient values between measured variables of muscle and tendon and chronological or skeletal ages.
Keywords: strain; hysteresis; cross-sectional area; skeletal age